2005
DOI: 10.1007/s00392-005-0281-7
|View full text |Cite
|
Sign up to set email alerts
|

Female patient with proximal myotonic myopathy and ventricular tachycardia

Abstract: A 68-year-old woman with known proximal myotonic myopathy was transferred to our hospital for further diagnostic and therapeutic evaluation after successful termination of an episode of sustained ventricular tachycardia. In 2001, the myopathy was diagnosed after symptomatic weakness of the hip flexors. A cardiomyopathy with slight reduction of systolic left ventricular function was found in 2002. Coronary angiography excluded relevant coronary artery disease. The electrophysiologic examination could provoke at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…One study found that paroxysmal atrial fibrillation occurred in 16% of patients, mild left ventricular dysfunction occurred in 10%, and frank congestive heart failure occurred in 5% . Rare cases of SCD, presumably resulting from ventricular arrhythmias, have also been reported in DM2 …”
Section: Muscular Dystrophies With Prominent Cardiac Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that paroxysmal atrial fibrillation occurred in 16% of patients, mild left ventricular dysfunction occurred in 10%, and frank congestive heart failure occurred in 5% . Rare cases of SCD, presumably resulting from ventricular arrhythmias, have also been reported in DM2 …”
Section: Muscular Dystrophies With Prominent Cardiac Involvementmentioning
confidence: 99%
“…56 Rare cases of SCD, presumably resulting from ventricular arrhythmias, have also been reported in DM2. 58,59 Emery-Dreifuss Muscular Dystrophy. Emery-Dreifuss muscular dystrophy (EDMD) is a rare disorder with X-linked (EDMD1), autosomal dominant (AD; EDMD2) and, rarely, autosomal recessive (AR) inheritance.…”
Section: Pathophysiologymentioning
confidence: 99%